Only the brave? : Risk and time preferences of decision makers and firms' investment in worker training - Jansen, Anika [Verfasser]; Pfeifer, Harald [Verfasser]; Raecke, Julia [Verfasser] (My University, 2017)
"In this paper, we study the relation between decision makers' preferences and training investments of their firms. First, we develop a theoretical framework, which takes the possibility into account that individual preferences of decision makers may influence firm behavior with respect to training. We then develop and test the hypothesis that the willingness to take risks or the preference for future profits of decision makers is positively related and procrastination negatively related to firms’ investment in worker training. Using unique firm-level data, including both person-level preference measures and firm-level information about training costs, we find empirical support for our hypothesis. Training investment is higher in firms with risk-inclined decision makers and lower in firms with procrastinating decision makers. The preference for future profits is relevant for training participation and the number of trained workers, but not for the training investment per worker. The results imply that firms have scope to adjust their profit-maximizing strategies by taking the individual preferences of their decision makers into account." (Authors' abstract, BIBB-Doku)
Außerdem veröffentlicht als "Swiss Leading House Working Paper No. 124", http://repec.business.uzh.ch/RePEc/iso/leadinghouse/0124_lhwpaper.pdf [Zugriff 13.3.2018]
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.1.1 Ausbildungsstellenmarkt; S 3.2 Unternehmen und Behörden; Ausbildungsinvestition; Betriebliche Berufsausbildung; Ausbildungsbetrieb; Ausbildungsverhalten; Ökonomische Faktoren